Identification of a biosynthetic gene cluster for the polyene macrolactam sceliphrolactam in a Streptomyces strain isolated from mangrove sediment - Hoang, Kim Le Mai (2018)
Streptomyces are a genus of Actinobacteria capable of producing structurally diverse natural products. Here we report the isolation and characterization of a biosynthetically talented Streptomyces (Streptomyces sp. SD85) from tropical mangrove sediments. Whole-genome sequencing revealed that Streptomyces sp. SD85 harbors at least 52 biosynthetic gene clusters (BGCs), which constitute 21.2% of the 8.6-Mb genome. When cultivated under lab conditions, Streptomyces sp. SD85 produces sceliphrolactam, a 26-membered polyene macrolactam with unknown biosynthetic origin. Genome mining yielded a putative sceliphrolactam BGC (sce) that encodes a type I modular polyketide synthase (PKS) system, several β-amino acid starter biosynthetic enzymes, transporters, and transcriptional regulators. Using the CRISPR/Cas9–based gene knockout method, we demonstrated that the sce BGC is essential for sceliphrolactam biosynthesis. Unexpectedly, the PKS system encoded by sce is short of one module required for assembling the 26-membered macrolactam skeleton according to the collinearity rule. With experimental data disfavoring the involvement of a trans-PKS module, the biosynthesis of sceliphrolactam seems to be best rationalized by invoking a mechanism whereby the PKS system employs an iterative module to catalyze two successive chain extensions with different outcomes. The potential violation of the collinearity rule makes the mechanism distinct from those of other polyene macrolactams.